Primerjalni frazemi z zoonimnimi sestavinami v prekmurskem narečju in makedonščini - Koletnik, Mihaela; Nikolovski, Gjoko (Slavia Centralis, 2020)
COMPARATIVE IDIOMS WITH ANIMAL COMPONENTS IN THE PREKMURJE DIALECT AND MACEDONIANThe article deals with comparative idioms, a component of which is the naming of animals. Slovenian Prekmurje dialect idioms are compared to idioms in the genetically related Macedonian language. Here we make use of the dictionary of comparative idioms (Hrvatsko-slavenski rječnik poredbenih frazema (2006); Slovenian part by Erika Kržišnik) and Macedonian Phraseology Dictionary (Фразеолошки речник на македонскиот јазик (2003; 2008; 2009)) and determine the similarities and differences between them. Contrasting Prekmurje dialect idioms and Macedonian ones shows which images generate the same idiomatic meaning in both compared languages and whether the same (established, real, alleged and frequently also anthropomorphically ascribed) characteristics of individual animals were motivational at the time of their creation.
Keywords: phraseology; animal idioms; Slovenian; Prekmurje dialect; Macedonian